Evaluation of fine needle aspiration cytology in the diagnosis of head and neck masses and its correlation with histopathological findings - Thakur, Ajay Singh; Gahine, Renuka; Kulkarni, Vishal (International Journal of Advances in Medicine, 2016)
Background: A number of masses may develop in the head and neck region and these can also be called swellings, growths, tumors or lumps. Various diseases may affect head and neck region, which present clinically as swellings. Commonly presenting head and neck masses occur within the thyroid, salivary glands and lymph nodes. The evaluation of head and neck mass is a common clinical dilemma and a condition which clinicians routinely encounter. It is evident that their early diagnoses provide the best chance of successful treatment. FNAC is a simple, quick and cost effective method to sample superficial masses found in the head and neck region. An early differentiation of benign from malignant pathology greatly influences the planned treatment. FNAC can be both diagnostic and therapeutic in cystic swellings. Methods: The present Retro prospective study (Prospective for one year from January 2013 to December 2013 along with five year retrospective from January 2008 to December 2012) was carried out in the Department of Pathology, Pt. J.N.M. Medical College and associated Dr. B.R.A.M. Hospital, Raipur. Cases for prospective study were selected from patients presented with head and neck masses attending the ENT OPD and indoor patients. Two techniques were used to perform FNAC. (Aspiration technique and Non-aspiration technique) After FNAC of head and neck lesions follow up of cases was done for histopathological examination. Final histopathological diagnosis was compared with the FNAC findings to assess the accuracy of cytodiagnosis. Results: A total of 12,514 FNACs done during six years, 1874 (14.9%) cases were diagnosed as head and neck lesions. Of the total 1874 cases of head and neck lesions, lymph node lesions were the commonest, accounting for 50.8% of cases. Thyroid and salivary gland lesions constituted 32.6% and 10.4% respectively. Analysis of FNAC of thyroid lesions, discordance was found more in malignant (11.8%) as compared to benign lesions, while Discordance was found more in benign lesion (12.4%) as compared to malignant lesion aspirates in lymph node lesions. Conclusions: FNAC is having a high diagnostic rate to differentiate benign and malignant lesions.